Status, image, standing and so on: a conceptual framework to systematise attractiveness of vocational education and training - Pilz, Matthias [Verfasser] (My University, 2025)
„The status and attractiveness of vocational education and training (VET) is increasingly the focus of public debate internationally. A closer analysis of the literature on the topic makes it clear that many different terms are used, some with different understandings. What is hidden in the academic discussion behind terms such as status, standing or even attractiveness, image or esteem is diffuse in many respects. This article takes up this problem by first taking up the academic literature on the definition of the term and critically reviewing it. In a second step, a structural approach is presented which contextualises the various concepts from the perspective of different actors. The focus here is not to be tailored to single institutions or to individual countries or world regions. To achieve a structuring of the different approaches, the model design is thus to be made by means of an approach that is orientated towards an actor model and takes motivation-theoretical aspects into account. Consequently, this approach offers a link between individual behaviour and external factors. At the same time, it enables the localisation of various education policy instruments that influence VET in terms of attractiveness. The model might not fit into all different country-specific conditions and need a socio-cultural adaption in line with the local or regional framing. At the same time, it enables the localisation of various education policy instruments that influence VET in terms of attractiveness.“ (author’s abstract; BIBB-Doku)
OnlineFirst 10. April 2025
Keywords: S 1 Stufen der Berufsbildung; 370; Berufsbildung; Attraktivität; Begriff; Literaturanalyse